EKSISTENSI PENGADILAN PAJAK SEBAGAI BADAN PERADILAN DI INDONESIA - CH. Anggia H.D.K.W. (Perspektif, 2005)
Recently, the existence of Tax Court has increased discussion comparing with the existing State Administrator Court. The independence of Tax Court can be explained that it is the only Court that has particular duty to handle the tax dispute. It has the place to do its juridical function, although at first, as stated in Tax Directorate General eq. Letter of Tax Assessment, the Tax Court was doing the Executive Function only. In term of doing its function, the Tax Court has the independence to make a verdict without decision of any other official office, as clarified in ps. 86 UU No. 14 th. 2002.